Celebrates (Raton Range Raton, New Mexico, 1980)
Newspaper Article on the 101st birthday of Anna Rice.
Master list item #: 21
File location is in the Raton File Cabinet
Keywords: Rice, Anna; Miner's Hospital; Local History; Biography; Life and Customs; Birthday; Celebration; Raton, New Mexico; Denmark